The Impact of R&D Input on Technological Innovation: Evidence from South Asian and Southeast Asian Countries - Lei Lv; Yuchen Yin; Yuanchang Wang (Discrete Dynamics in Nature and Society, 2020)
In the era of the rapid development of knowledge economy and science, all countries have thought highly of technical innovation and greatly increased the R&D input for it. However, the research on the impact of R&D input on technical innovation lacks specialized, cross-country, and cross-time investigations, and especially, the research on small countries such as South Asia and Southeast Asia where technical innovation is relatively backward. So, does R&D input in South Asia and Southeast Asia have an impact on technical innovation and to what extent? Let us analyze the panel data of 18 countries in South Asia and Southeast Asia from 2001 to 2018, use three methods of unit root test to test the stationarity of variables, adopt the Kao cointegration test to test a stable long-term relationship between the variables, and then, respectively, carry out the transnational regression analysis of the difference between patent applications, scientific journal articles, and the R&D input with multiple models. Finally, the heteroscedasticity robust fixed-effect model is found to be the most suitable for this study after the comparative analysis of multiple models. Through the fixed-effect intercepts of each country in the heteroscedasticity robust fixed-effect models, South Asian and Southeast Asian countries are divided into three levels, and each level lists a set of equations. So, the following conclusions are drawn: both R&D expenditure and manpower input in South Asia and Southeast Asia significantly promote technological innovation; the efficiency of both R&D expenditure and manpower input promoting technological innovation in South Asia and Southeast Asia is low and needs to be improved. These conclusions provide references for policymakers in some countries where technological innovation is relatively backward, especially in Cambodia, Lao PDR, Myanmar, Timor-Leste, Bangladesh, Bhutan, Maldives, and Nepal.